Analisis Aspek yang Mempengaruhi Ketertarikan Siswa SMA dalam Pembelajaran Biologi - Weyni Iskandaria; Miza Nina Adlini; Siti Nur Annisa Boang Manalu; Sari Putri Ramadani Tambunan; Dita Khairanti; Adella Shaharani (Universitas Nusantara PGRI Kediri, 2023)
Interest in learning is important in supporting student academic achievement. This often happens in biology subjects in the classroom. Many students expressed boredom in the lesson. Therefore, researchers will dig deeper related to aspects of student's interest in biology learning. The method used is literature study, which analyzes previous research. The results obtained are factors that influence student learning interest in biology subjects depends on student interest in teachers when teaching, interest in biology subjects, feeling happy with the way teachers teach and delivering material, attention to biology subjects, and being involved in the learning process and student tenacity when learning. In addition, internal factors (physical health, drive, arousal, and grasping ability) and external influences (environment, parents, teachers, learning styles, etc.) can affect students' interest in learning, the most important in interest in learning biology in the classroom is the initial and strong intention that students have when learning biology begins in class